Teologi Pembebasan dalam Perspektif Nahdlatul Ulama Subang: Sebuah Analisis Gerakan Sosial dan Kesadaran Kritis - Firmansyah, Muhammad Iqbal (Kongregasi Hati Kudus Yesus (RSCJ) Indonesia, 2025)
This study aims to explore the implementation of liberation theology within Nahdlatul Ulama (NU), focusing on how religious values are integrated with social actions to address issues such as poverty, injustice, and structural oppression in the local context. For empirical evidence, the author focuses on the application of theology within Nahdlatul Ulama Subang, West Java. This study employs a qualitative approach, with data collection techniques including in-depth interviews, observations, and document analysis. The findings indicate that NU, particularly in Subang, adopts a substantialistic and rationalistic approach to liberation theology, focusing on empowering marginalized communities through critical awareness education, zakat- and infaq-based economic programs, and social advocacy. This approach has strengthened NU's role as an agent of social transformation at the local level, despite challenges such as structural resistance and internal organizational dynamics. This research contributes to the understanding of liberation theology as both an ideological and practical framework that aligns religious values with contemporary social justice efforts, while demonstrating the flexibility of religion to adapt to the needs of the times while preserving its spiritual essence.